2018
DOI: 10.1111/jpm.12505
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of affiliate stigma among family caregivers of people with mental illness: A systematic review and meta‐analysis

Abstract: Accessible Summary What is known on the subject? A growing body of qualitative and quantitative research has investigated the experiences of affiliated stigma for family members of PWMI. Some findings are contradictory and have not been considered systematically. What does the paper adds to existing knowledge? Family caregivers of PWMI may encounter affiliate stigma, but no systematic review or meta‐analysis has been conducted to evaluate affiliate stigma among them. We identified eight variables signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 58 publications
2
41
1
8
Order By: Relevance
“…Affiliate stigma may result in more serious consequences than courtesy stigma does [16]. Affiliate stigma may not only enhance caregivers' psychological distress and reduce their quality of life [17,18] but also abate the care they provide for affiliated people and cooperation with health care professionals [19]. It is crucial to evaluate and reduce affiliate stigma among caregivers of people with mental illness [20].…”
Section: Affiliate Stigma In Caregivers Of People With Mental Illnessmentioning
confidence: 99%
See 3 more Smart Citations
“…Affiliate stigma may result in more serious consequences than courtesy stigma does [16]. Affiliate stigma may not only enhance caregivers' psychological distress and reduce their quality of life [17,18] but also abate the care they provide for affiliated people and cooperation with health care professionals [19]. It is crucial to evaluate and reduce affiliate stigma among caregivers of people with mental illness [20].…”
Section: Affiliate Stigma In Caregivers Of People With Mental Illnessmentioning
confidence: 99%
“…A growing body of research has investigated affiliate stigma in family caregivers of people with schizophrenia, depression, or affective disorders [19]. These studies have not only demonstrated that affiliate stigma is prevalent among family caregivers but also revealed that health-focused interventions for caregivers can reduce the effect of affiliate stigma by providing social support from medical professionals [19]. However, few studies have focused on affiliate stigma in family caregivers of children with ADHD.…”
Section: Affiliate Stigma In Caregivers Of Children With Adhdmentioning
confidence: 99%
See 2 more Smart Citations
“…They feel the stigma directed toward the person with the mental illness, and the stigma directed toward the families. 9 Disparities on the local level can be addressed by behavioral health nursing presence in the community. Community mental health support systems vary considerably across the county, and the resources need to be available, updated, and disseminated to all who need service.…”
Section: Community Resources: How Have You Used the Community Resourcmentioning
confidence: 99%